Adaptive agricultural practices : building resilience in a changing climate - Dubey, Pradeep Kumar (SpringerBriefs in environmental science, 2020)
This brief explores several adaptive agricultural practices from around the world to fulfill current and future agricultural demands for food security due to the challenges posed by climate change and growing global population. Readers will discover how farmers adapt to environmental changes by adopting various agronomic practices at crop, farm and landscape levels. Particular attention is given to systemic and transformational adaptation strategies employed by farmers such as mulching, organic farming and crop diversification. This is a highly informative and carefully presented book that provides insights on how crops can build up resilience against periods of drought, high salinity, disasters such as floods, and diseases. The policy implications and future prospects of these adaptation strategies are also addressed. Environmental and plant scientists, agronomists and researchers in climate sciences will find this book interesting.